Children of laughter and the re-creation of humanity: the theological vision and logic of Paul's letter to the Galatians - Tedder, Samuel J. (Wipf and Stock Publishers, 2020)
Intro -- Title Page -- Tables and Figures -- Foreword -- Preface -- Acknowledgments -- Abbreviations -- Chapter 1: Introduction -- Chapter 2: Galatians 4:21-5:1 as the Vantage Point -- Chapter 3: The Theological Potential in the Abraham Narrative -- Chapter 4: The Theological Potential in Isaiah's Vision of Restoration -- Chapter 5: Paul's Allegorical Practice in Galatians 4:21-5:1 -- Chapter 6: Configuring The Theological Vision and Logic of Galatians from the Vantage Point of 4:21-5:1 -- Chapter 7: Conclusions -- Appendix -- Bibliography.